The asymmetric effects of monetary policy in four Asian economies. - Tan, Siow Hooi; Habibullah, Muzafar Shah; Smith, Peter (Universiti Putra Malaysia, 2008)
The idea that the effectiveness of monetary policy measures may depend on the state of the economy is examined for four Asian economies using a generalized Hamilton Markov switching model of output due to Garcia and Schaller (2002). The null hypothesis of symmetry is rejected for these economies and monetary policy is seen to have larger effects during downturns than during upswings.